2018
DOI: 10.1177/0961463x18763688
|View full text |Cite
|
Sign up to set email alerts
|

‘Time … lost time’: Exploring how partners of long-term prisoners experience the temporal pains of imprisonment

Abstract: This article identifies and examines the temporal pains of imprisonment as experienced by female partners of male long-term prisoners in the UK. Drawing on in-depth interviews with 33 women, it discusses how long sentences interrupted the women's normative life courses, shaped their daily lives, and resulted in them having to negotiate living within both prison time and outside time. It also highlights the need to go beyond the focus on concentrated family time and consider the extent to which prisoners and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 22 publications
0
23
0
3
Order By: Relevance
“…Since Sykes’ (1958) classic study, authors around the world, studying different groups of prisoners, have analyzed historical iterations and socially-nuanced versions of the pains of imprisonment (e.g. in relation to long-term prisoners (Kotova, 2019; Leigey and Ryder, 2015); racialized prisoners (Ugelvik, 2014); immigration detainees (Longazel et al, 2016; Ugelvik and Damsa, 2018); young persons (Cox, 2011; Fagan and Kupchik, 2011) and gender (Crewe et al, 2017; Ricciardelli, 2015; Soffer and Ajzenstadt, 2010). This scholarship is underpinned by the recognition that the pains of imprisonment are neither static nor universal, but rather, are shaped by social-structural, institutional, and personal factors.…”
Section: The Pains Of Releasementioning
confidence: 99%
“…Since Sykes’ (1958) classic study, authors around the world, studying different groups of prisoners, have analyzed historical iterations and socially-nuanced versions of the pains of imprisonment (e.g. in relation to long-term prisoners (Kotova, 2019; Leigey and Ryder, 2015); racialized prisoners (Ugelvik, 2014); immigration detainees (Longazel et al, 2016; Ugelvik and Damsa, 2018); young persons (Cox, 2011; Fagan and Kupchik, 2011) and gender (Crewe et al, 2017; Ricciardelli, 2015; Soffer and Ajzenstadt, 2010). This scholarship is underpinned by the recognition that the pains of imprisonment are neither static nor universal, but rather, are shaped by social-structural, institutional, and personal factors.…”
Section: The Pains Of Releasementioning
confidence: 99%
“…I was, however, surprised that work on families of people serving long sentences was not engaged with. Although the authors discuss the impact of life sentences on familial relationships, my own work (Kotova, 2019) on partners of men serving long sentences and Annison and Condry’s (2018) work on families of people subject to Imprisonment for Public Protection sentences further reinforce the findings of Crewe and his colleagues. For instance, my research found that long sentences similarly disrupted the life course of partners outside and created a sense of temporal disconnect.…”
mentioning
confidence: 61%
“…For example, they discuss the destruction of future plans, such as holidays, plans of employment and other expected biographical milestones. Arguably, more could have been done with this by drawing on sociology of the life course and gender – for instance, themes of loss of motherhood and ageing may be especially prominent for women serving life sentencing due to the social construction of womanhood as being centred on youth, beauty and motherhood (see Kotova, 2019 in the context of women whose partners are serving long prison sentences).…”
mentioning
confidence: 99%
“…The waiting and loss of temporal autonomy particularly emerges out of uncertainty and unpredictability, especially during custody or detention (Turnbull, 2016). In this context, Kotova (2018) develops the notion of temporal pains of imprisonment to analyse the experiences by female partners of long-term incarcerated individuals in the United Kingdom. She argues that the prison time extends beyond the visitation time and that research also needs to consider the deprivation of mundane family experiences as a consequence of the prison sentence.…”
Section: Diverging Temporalities Of the Smart Prisonmentioning
confidence: 99%